Anti-cracking copper rare earth alloy and preparation method thereof

By using a specific proportion of cerium and yttrium as rare earth elements in copper rare earth alloys and adopting a specific preparation process, the problem of prone to cracking in copper rare earth alloys during processing is solved, which significantly improves the tensile strength, elongation and yield strength of the alloy, and enhances its cracking resistance.

CN119753416AActive Publication Date: 2025-04-04鹤山市金益铜业有限公司
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411781483.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Copper rare earth alloys are prone to cracking problems during processing, resulting in poor hot processing performance and difficulty in cold processing.

Method used

A copper rare earth alloy consisting of chromium, titanium, manganese, antimony, zirconium and rare earth elements are used. The rare earth elements are composed of cerium and yttrium in a specific proportion, and through specific smelting and casting processes, including smelting, refining, slag removal, adding rare earth mixtures and insulating casting, a copper rare earth alloy that is resistant to cracking is prepared.

Benefits of technology

Effectively refine the alloy grains, reduce the tendency of thermal cracking, improve tensile strength, elongation and yield strength, and enhance the cracking resistance of the alloy.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an anti-cracking copper rare earth alloy and a preparation method thereof, belongs to the technical field of alloys, and is characterized in that the anti-cracking copper rare earth alloy comprises the following components in percentage by mass: 0.5-1.2% of chromium, 0.2-0.5% of titanium, 0.2-0.4% of manganese, 0.8-1.5% of antimony, 0.2-0.7% of zirconium, 0.4-1.5% of rare earth elements and the balance of copper and inevitable impurities. The rare earth element is composed of cerium and yttrium according to the weight ratio of (0.5-1): (0.2-0.5), and the technical effect of solving the problem of cracking during copper-rare earth alloy machining is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloys, and in particular to a crack-resistant copper-rare earth alloy and a preparation method thereof. Background Art

[0002] Copper is an important nonferrous metal material with excellent electrical and thermal conductivity, good corrosion resistance and excellent processing performance. It is widely used in power electronics, petrochemicals, machinery manufacturing, national defense, household appliances and construction industries. Copper rare earth alloy is a composite material containing rare earth elements, copper and other alloy elements. This alloy has a wide range of applications in aerospace, automobile manufacturing, electronics industry, nuclear industry, metallurgy and other fields due to its unique physical and chemical properties.

[0003] The role of rare earth elements in copper alloys is mainly to purify the melt through degassing, deoxidation, impurity removal and slag formation, thereby improving the performance of copper alloys. However, in the preparation of copper alloys, rare earths will preferentially combine with copper to form a brittle low-melting eutectic structure that is enriched at the grain boundaries. Therefore, the hot working performance of copper alloys is poor and cracking is prone to occur during cold working. Summary of the invention

[0004] In order to solve the problem of cracking during processing of copper-rare earth alloy, the present invention provides a crack-resistant copper-rare earth alloy and a preparation method thereof.

[0005] The first aspect of the present invention is to provide a crack-resistant copper rare earth alloy, which adopts the following technical solution: A crack-resistant copper rare earth alloy is composed of the following components in percentage by mass: 0.5-1.2% chromium, 0.2-0.5% titanium, 0.2-0.4% manganese, 0.8-1.5% antimony, 0.2-0.7% zirconium, 0.4-1.5% rare earth elements, and the balance is copper and unavoidable impurities. The rare earth elements are composed of cerium and yttrium in a weight ratio of (0.5-1):(0.2-0.5).

[0006] Preferably, the weight ratio of cerium to yttrium is 0.8:0.3.

[0007] The second aspect of the present invention is to provide a method for preparing a crack-resistant copper-rare earth alloy, comprising the following steps: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1400-1500°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1500-1550°C, chromium is added and smelting is continued to obtain a refined liquid; S3. After slagging, continue refining at this temperature for 8-10 minutes, then turn off the power and let it stand for 12-15 minutes, then add the rare earth mixture and allow the rare earth mixture to enter the bottom of the refined liquid, then stir evenly and heat to 1100℃ for casting.

[0008] Preferably, the heat-insulating casting is as follows: the casting furnace is heated to 900-1000° C. and then the mold is loaded for casting. The casting speed is 260-280 r / min and the pitch is adjusted to 4-5 mm.

[0009] Preferably, the material after the induction casting is introduced into a drawing process to carry out a segregation layer peeling process, the drawing amount is 0.8-1.4 mm, and after drawing, it is straightened with a straightening machine to obtain an ingot.

[0010] Preferably, the ingot is subjected to homogenization, hot rolling, cold rough rolling, intermediate annealing, cold finish rolling and aging treatment in sequence to obtain the copper rare earth alloy material.

[0011] Preferably, the homogenization treatment temperature is 920-950° C. for homogenization annealing and insulation for 4-6 hours.

[0012] Preferably, the intermediate annealing is performed at 460±10° C. for 8-10 h.

[0013] Preferably, the aging treatment is carried out at 520±10°C for 6-10 hours.

[0014] Preferably, the average particle size of the rare earth mixture is 30-50 μm.

[0015] Too high a furnace temperature can cause serious ablation of rare earths, reducing the recovery rate of rare earths. In summary, the present invention has the following beneficial effects: 1. Rare earth elements can effectively refine alloy grains, and the generated second phase is beneficial to reducing the thermal cracking tendency of the alloy. The combination of rare earth elements cerium and yttrium in the present application makes the microstructure of the alloy fine and more evenly distributed, so that a large number of intercrystalline bridges are formed. A large number of bridges are beneficial to resist the stress generated when the grains separate from each other, thereby improving the alloy's resistance to cracking. When excessive cerium and yttrium are added, the microstructure of the alloy does not continue to be refined but coarsens. At the same time, the second phase at the grain boundary increases significantly, and the intercrystalline triangle area becomes larger. It can be seen that excessive cerium and yttrium will segregate at the grain boundary of the alloy and precipitate a large amount of second phases. The precipitation of a large amount of second phases easily blocks the shrinkage channel generated by the alloy when it is stressed, thereby causing the alloy to have a high tendency to thermal cracking. Therefore, when the rare earth elements in the present application are composed of cerium and yttrium in a weight ratio of (0.5-1): (0.2-0.5), the cracking resistance of the copper rare earth alloy can be effectively improved.

[0016] 2. The combined use of chromium, titanium, manganese, antimony and zirconium elements in this application helps to improve the overall performance of the copper rare earth alloy, refine the alloy grains, improve the strength and toughness of the copper rare earth alloy, and reduce the thermal cracking tendency of the copper rare earth alloy.

[0017] 2. In the present application, when the particle size of the rare earth mixture is limited to between 30-50 μm, the absorption rate of the rare earth can be effectively improved, the burn-off rate can be reduced, and the rare earth can be distributed more evenly in the alloy, thereby improving the anti-cracking effect of the alloy. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below with reference to the embodiments.

[0019] The first aspect of the present invention is to provide a crack-resistant copper rare earth alloy, which adopts the following technical solution: A crack-resistant copper rare earth alloy is composed of the following components in percentage by mass: 0.5-1.2% chromium, 0.2-0.5% titanium, 0.2-0.4% manganese, 0.8-1.5% antimony, 0.2-0.7% zirconium, 0.4-1.5% rare earth elements, and the balance is copper and unavoidable impurities. The rare earth elements are composed of cerium and yttrium in a weight ratio of (0.5-1):(0.2-0.5).

[0020] Preferably, the weight ratio of cerium to yttrium is 0.8:0.3.

[0021] The second aspect of the present invention is to provide a method for preparing a crack-resistant copper-rare earth alloy, comprising the following steps: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1400-1500°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1500-1550°C, chromium is added and smelting is continued to obtain a refined liquid; S3. After slagging, continue refining at this temperature for 8-10 minutes, then turn off the power and let it stand for 12-15 minutes, then add the rare earth mixture and allow the rare earth mixture to enter the bottom of the refined liquid, then stir evenly and heat to 1100℃ for casting.

[0022] Preferably, the heat-insulating casting is as follows: the casting furnace is heated to 900-1000° C. and then the mold is loaded for casting. The casting speed is 260-280 r / min and the pitch is adjusted to 4-5 mm.

[0023] Preferably, the material after the induction casting is introduced into a drawing process to carry out a segregation layer peeling process, the drawing amount is 0.8-1.4 mm, and after drawing, it is straightened with a straightening machine to obtain an ingot.

[0024] Preferably, the ingot is subjected to homogenization, hot rolling, cold rough rolling, intermediate annealing, cold finish rolling and aging treatment in sequence to obtain the copper rare earth alloy material.

[0025] Preferably, the homogenization treatment temperature is 920-950° C. for homogenization annealing and insulation for 4-6 hours.

[0026] Preferably, the intermediate annealing is performed at 460±10° C. for 8-10 h.

[0027] Preferably, the aging treatment is carried out at 520±10°C for 6-10 hours.

[0028] Preferably, the average particle size of the rare earth mixture is 30-50 μm.

[0029] Example 1 A method for preparing a crack-resistant copper-rare earth alloy, the copper-rare earth alloy consisting of the following components in mass percentage: 0.5% chromium, 0.2% titanium, 0.2% manganese, 0.8% antimony, 0.2% zirconium, 0.4% rare earth elements, and the balance being copper and unavoidable impurities, wherein the rare earth elements consist of cerium and yttrium in a weight ratio of 0.5:0.2; The preparation method comprises the following steps: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1400°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1500°C, chromium is added and smelted to obtain a refined liquid; S3, at a temperature of 1100-℃, continue refining at this temperature for 8 minutes after slagging, then turn off the power and let it stand for 12 minutes, then add a rare earth mixture with an average particle size of 30μm, and let the rare earth mixture enter the bottom of the refined liquid, then stir evenly and heat it to 1100℃ and introduce it into the casting furnace. After heating the casting furnace to 900℃, start loading the mold for casting, the casting speed is 260r / min, and the pitch is adjusted to 4-5mm; S4, introducing the casted material into a drawing process to perform a segregation layer peeling process, the drawing amount is 0.8 mm, and after drawing, the material is straightened with a straightening machine to obtain an ingot; S5. After homogenizing and annealing the ingot obtained in step S4 at 920° C. for 4 hours, hot rolling is performed at 700° C. to 14 mm, and then rough cold rolling is performed to a thickness of 0.8 mm. Intermediate annealing is performed at 460±10° C. for 8 hours, and cold finishing rolling is performed to a thickness of 0.3 mm. After aging treatment is performed at 520±10° C. for 6 hours, a copper rare earth alloy material is obtained.

[0030] Example 2 A method for preparing a crack-resistant copper-rare earth alloy, the copper-rare earth alloy consisting of the following components in mass percentage: 0.5% chromium, 0.2% titanium, 0.2% manganese, 0.8% antimony, 0.2% zirconium, 0.4% rare earth elements, and the balance being copper and unavoidable impurities, wherein the rare earth elements consist of cerium and yttrium in a weight ratio of 0.5:0.2; The preparation method comprises the following steps: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1450°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1500°C, chromium is added and smelted to obtain a refined liquid; S3. After slagging, continue refining at this temperature for 8 minutes, then turn off the power and let it stand for 15 minutes, then add a rare earth mixture with an average particle size of 30 μm, and allow the rare earth mixture to enter the bottom of the refined liquid, then stir evenly and heat it to 1100°C before introducing it into the casting furnace. After heating the casting furnace to 950°C, start loading the mold for casting, the casting speed is 270r / min, and the pitch is adjusted to 4-5mm; S4, introducing the casted material into a drawing process to perform a segregation layer peeling process, the drawing amount is 1.1 mm, and after drawing, the material is straightened with a straightening machine to obtain an ingot; S5. The ingot obtained in step S4 is homogenized and annealed at 940° C. for 5 h, then hot-rolled to 14 mm at 800° C., rough-cold rolled to 1.0 mm thick, intermediate annealed at 460±10° C. for 9 h, cold-finished rolled to 0.5 mm thick, and aged at 520±10° C. for 8 h to obtain a copper rare earth alloy material.

[0031] Example 3 A method for preparing a crack-resistant copper-rare earth alloy, the copper-rare earth alloy consisting of the following components in mass percentage: 0.5% chromium, 0.2% titanium, 0.2% manganese, 0.8% antimony, 0.2% zirconium, 0.4% rare earth elements, and the balance being copper and unavoidable impurities, wherein the rare earth elements consist of cerium and yttrium in a weight ratio of 0.5:0.2; The preparation method comprises the following steps: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1500°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1550°C, chromium is added and smelted to obtain a refined liquid; S3, at a temperature of 1150°C, continue refining at this temperature for 10 minutes after slagging, then turn off the power and let it stand for 15 minutes, then add a rare earth mixture with an average particle size of 30 μm, and allow the rare earth mixture to enter the bottom of the refined liquid, then stir evenly and heat it to 1100°C and introduce it into the casting furnace. After heating the casting furnace to 1000°C, start loading the mold for casting, the casting speed is 280r / min, and the pitch is adjusted to 4-5mm; S4, introducing the casted material into the drawing process to carry out the segregation layer peeling process, the drawing amount is 1.4 mm, and after drawing, the material is straightened by a straightening machine to obtain an ingot; S5. After homogenizing and annealing the ingot obtained in step S4 at 950° C. for 6 hours, hot rolling is performed at 920° C. to 15 mm, and then rough cold rolling is performed to a thickness of 1.0 mm. Intermediate annealing is performed at 460±10° C. for 10 hours, and cold finishing rolling is performed to a thickness of 0.5 mm. After aging treatment is performed at 520±10° C. for 10 hours, a copper rare earth alloy material is obtained.

[0032] Example 4 A method for preparing a crack-resistant copper rare earth alloy, the copper rare earth alloy consisting of the following components in mass percentage: 0.9% chromium, 0.3% titanium, 0.3% manganese, 1.2% antimony, 0.5% zirconium, 1.0% rare earth elements, and the balance being copper and unavoidable impurities, wherein the rare earth elements consist of cerium and yttrium in a weight ratio of 0.5:0.2; The preparation method comprises the following steps: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1450°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1500°C, chromium is added and smelted to obtain a refined liquid; S3. After slagging, continue refining at this temperature for 8 minutes, then turn off the power and let it stand for 15 minutes, then add a rare earth mixture with an average particle size of 30 μm, and allow the rare earth mixture to enter the bottom of the refined liquid, then stir evenly and heat it to 1100°C before introducing it into the casting furnace. After heating the casting furnace to 950°C, start loading the mold for casting, the casting speed is 270r / min, and the pitch is adjusted to 4-5mm; S4, introducing the casted material into a drawing process to perform a segregation layer peeling process, the drawing amount is 1.1 mm, and after drawing, the material is straightened with a straightening machine to obtain an ingot; S5. The ingot obtained in step S4 is homogenized and annealed at 940° C. for 5 h, then hot-rolled to 14 mm at 800° C., rough-cold rolled to 1.0 mm thick, intermediate annealed at 460±10° C. for 9 h, cold-finished rolled to 0.5 mm thick, and aged at 520±10° C. for 8 h to obtain a copper rare earth alloy material.

[0033] Example 5 A method for preparing a crack-resistant copper rare earth alloy, the copper rare earth alloy consisting of the following components in percentage by mass: 1.2% chromium, 0.5% titanium, 0.4% manganese, 1.5% antimony, 0.7% zirconium, 1.5% rare earth elements, and the balance being copper and unavoidable impurities, wherein the rare earth elements consist of cerium and yttrium in a weight ratio of 0.5:0.2; The preparation method comprises the following steps: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1450°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1500°C, chromium is added and smelted to obtain a refined liquid; S3. After slagging, continue refining at this temperature for 8 minutes, then turn off the power and let it stand for 15 minutes, then add a rare earth mixture with an average particle size of 30 μm, and allow the rare earth mixture to enter the bottom of the refined liquid, then stir evenly and heat it to 1100°C before introducing it into the casting furnace. After heating the casting furnace to 950°C, start loading the mold for casting, the casting speed is 270r / min, and the pitch is adjusted to 4-5mm; S4, introducing the casted material into a drawing process to perform a segregation layer peeling process, the drawing amount is 1.1 mm, and after drawing, the material is straightened with a straightening machine to obtain an ingot; S5. The ingot obtained in step S4 is homogenized and annealed at 940° C. for 5 h, then hot-rolled to 14 mm at 800° C., rough-cold rolled to 1.0 mm thick, intermediate annealed at 460±10° C. for 9 h, cold-finished rolled to 0.5 mm thick, and aged at 520±10° C. for 8 h to obtain a copper rare earth alloy material.

[0034] Example 6 A method for preparing a crack-resistant copper rare earth alloy, which is different from Example 4 in that the weight ratio of cerium to yttrium in the rare earth elements is 0.8:0.3, and the rest is the same as Example 4.

[0035] Example 7 A method for preparing a crack-resistant copper rare earth alloy, which is different from Example 4 in that the weight ratio of cerium to yttrium in the rare earth elements is 1:0.5, and the rest is the same as Example 4.

[0036] Example 8 A method for preparing a crack-resistant copper rare earth alloy is different from Example 6 in that the average particle size of the rare earth mixture is 40 μm, and the rest is the same as Example 6.

[0037] Example 9 A method for preparing a crack-resistant copper rare earth alloy is different from Example 6 in that the average particle size of the rare earth mixture is 50 μm, and the rest is the same as Example 6.

[0038] Comparative Example 1 A method for preparing a crack-resistant copper rare earth alloy, which is different from Example 2 in that the rare earth elements are composed of lanthanum and yttrium in a weight ratio of 0.5:0.2, and the rest are the same as Example 2.

[0039] Comparative Example 2 A method for preparing a crack-resistant copper rare earth alloy, which is different from Example 2 in that the rare earth elements are composed of praseodymium and yttrium in a weight ratio of 0.5:0.2, and the rest are the same as Example 2.

[0040] Comparative Example 3 A method for preparing a crack-resistant copper rare earth alloy is different from that of Example 2 in that only cerium is used as the rare earth element, and the rest are the same as those of Example 2.

[0041] Comparative Example 4 A method for preparing a crack-resistant copper rare earth alloy is different from that of Example 2 in that only yttrium is used as the rare earth element, and the rest are the same as those of Example 2.

[0042] Comparative Example 5 A method for preparing a crack-resistant copper-rare earth alloy, which is different from Example 2 in that the copper-rare earth alloy contains no antimony, and the rest is the same as Example 2.

[0043] Performance Testing The copper rare earth alloys obtained in the above examples and comparative examples were tested for their performance, and the test results are shown in Table 1.

[0044] Table 1 Copper rare earth alloy performance test results project Tensile strength / MPa Elongation / % Yield strength / MPa Example 1 720 10.3 680 Example 2 724 10.8 685 Example 3 722 10.6 683 Example 4 733 11.4 692 Example 5 735 11.0 689 Example 6 736 11.6 693 Example 7 735 11.5 692 Example 8 737 11.7 694 Example 9 735 11.4 692 Comparative Example 1 720 9.3 667 Comparative Example 2 716 9.6 670 Comparative Example 3 706 7.8 654 Comparative Example 4 712 8.3 661 Comparative Example 5 718 9.8 673 From Table 1 we can see that: The tensile strength of the copper rare earth alloys obtained in Examples 1-3 of the present application is 720 MPa or above, the elongation is greater than 10%, and the yield strength is ≥680, indicating that the copper rare earth alloys obtained in the present application have good tensile strength, yield strength and elongation. The high tensile strength indicates that the copper rare earth alloy can withstand a large tensile force before fracture, and the elongation reflects the plastic deformation ability of the copper rare earth alloy before fracture. The higher the elongation, the better the toughness of the copper rare earth alloy, and the correspondingly enhanced crack resistance. Therefore, the copper rare earth alloys obtained in Examples 1-3 of the present application have good crack resistance.

[0045] Compared with Example 2, when the proportion of each component in the copper rare earth alloy is further increased, the tensile strength, elongation and yield strength of the copper rare earth alloy obtained in Example 4-5 are increased compared with Example 2. However, it can be seen from the test data in Example 5 that the elongation and yield strength of the copper rare earth alloy obtained in Example 5 are lower than those in Example 4. It can be seen that when the mass proportion of each component in the copper rare earth alloy is within the scope of the present application, it can effectively ensure that the rare earth alloy has good crack resistance.

[0046] Compared with Example 4, when the total amount of rare earth elements in the copper rare earth alloy remains unchanged, as the content of rare earth element cerium decreases, the tensile strength, elongation and yield strength of the copper rare earth alloy obtained in Example 7 are reduced compared with those in Example 6. Therefore, when the ratio of rare earth elements cerium and yttrium is within the range specified in this application, it can effectively ensure that the copper rare earth alloy has good crack resistance.

[0047] Compared with Example 6, as the average particle size of the rare earth mixture increases, the tensile strength, elongation and yield strength of the copper rare earth alloy obtained in Examples 8-9 are not much different from the tensile strength, elongation and yield strength in Example 6, indicating that when the average particle size of the rare earth mixture is within the range specified in this application, the absorption rate of rare earth elements can be effectively guaranteed and the burn-out rate can be reduced.

[0048] Compared with Example 2, when the rare earth elements are composed of lanthanum and yttrium or praseodymium and yttrium, or the rare earth elements are only cerium or yttrium, the tensile strength, elongation and yield strength of the copper rare earth alloys obtained in Comparative Examples 1-4 are significantly reduced compared with those in Example 2. It can be seen that the combined use of the rare earth elements cerium and yttrium in the present application effectively improves the crack resistance of the rare earth alloy.

[0049] Compared with Example 2, when antimony is lacking in the copper rare earth alloy component, the tensile strength, elongation and yield strength of the rare earth alloy obtained in Comparative Example 5 are lower than those in Example 2. It can be seen that the addition of antimony to the copper rare earth alloy can also effectively ensure that the copper rare earth alloy has good crack resistance.

[0050] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A crack-resistant copper rare earth alloy, characterized in that: The copper rare earth alloy is composed of the following components in percentage by mass: 0.5-1.2% chromium, 0.2-0.5% titanium, 0.2-0.4% manganese, 0.8-1.5% antimony, 0.2-0.7% zirconium, 0.4-1.5% rare earth elements, and the balance is copper and unavoidable impurities. The rare earth elements are composed of cerium and yttrium in a weight ratio of (0.5-1):(0.2-0.5).

2. The crack-resistant copper-rare earth alloy according to claim 1, characterized in that: The weight ratio of cerium to yttrium is 0.8:0.

3.

3. A method for preparing the crack-resistant copper-rare earth alloy according to claim 1 or 2, characterized in that: The steps include: S1. Smelting: fully melt the copper according to the mass percentage of the copper-rare earth alloy components; S2. After the copper is melted, the smelting temperature is raised to 1400-1500°C, titanium, manganese, antimony and zirconium are added, and then the temperature is further raised to 1500-1550°C, chromium is added and smelting is continued to obtain a refined liquid; S3. After slagging, continue refining at this temperature for 8-10 minutes, then turn off the power and let it stand for 12-15 minutes, then add the rare earth mixture and allow the rare earth mixture to enter the bottom of the refined liquid, then stir evenly and heat to 1100℃ for casting.

4. The method for preparing a crack-resistant copper-rare earth alloy according to claim 3, characterized in that: The heat-insulating casting is as follows: the casting furnace is heated to 900-1000° C. and then the mold is loaded for casting. The casting speed is 260-280 r / min and the pitch is adjusted to 4-5 mm.

5. The method for preparing a crack-resistant copper-rare earth alloy according to claim 4, characterized in that: The casted material is introduced into a drawing process to carry out a segregation layer peeling process, the drawing amount is 0.8-1.4 mm, and after drawing, it is straightened by a straightening machine to obtain an ingot.

6. The method for preparing a crack-resistant copper-rare earth alloy according to claim 5, characterized in that: The ingot is subjected to homogenization, hot rolling, cold rough rolling, intermediate annealing, cold finishing rolling and aging treatment in sequence to obtain a copper rare earth alloy material.

7. The method for preparing a crack-resistant copper-rare earth alloy according to claim 6, characterized in that: The homogenization treatment temperature is 920-950° C. for homogenization annealing and heat preservation for 4-6 hours.

8. The method for preparing a crack-resistant copper-rare earth alloy according to claim 6, characterized in that: The intermediate annealing condition is annealing at 460±10° C. for 8-10 hours.

9. The method for preparing a crack-resistant copper-rare earth alloy according to claim 6, characterized in that: The aging treatment conditions are to keep the temperature at 520±10°C for 6-10 hours.

10. The method for preparing a crack-resistant copper-rare earth alloy according to claim 3, characterized in that: The average particle size of the rare earth mixture is 30-50 μm.

Citation Information

Patent Citations

  • Novel environment-friendly high-stibium tin alloy pipe and preparation method thereof

    CN103045898A

  • High strength, high conductivity and high elongation copper alloy and preparation method thereof

    CN103382535A

  • High-strength, high-conductivity and high-extensibility rare earth copper alloy and preparation method thereof

    CN103388090A

  • Refrigerator mould copper alloy and preparation method thereof

    CN103397223A

  • High-performance copper-chromium alloy and preparation method thereof

    CN117821796A